The Impact of Digital Storytelling on Enhancing Speaking Skills - Ihsan, Muhammad Taufik (State Islamic University of Sultan Syarif Kasim Riau, 2024)
This research was conducted based on students’ problems in speaking, such as do not have self-esteem because the lack of courage students’, teacher strategy are boring, lack of vocabulary, feel hesitate in expressing idea because of the low capability in comprehension, error pronunciation, and low participation. Therefore, this research aimed to investigate the students’ speaking skill taught without and by using Digital Storytelling, to investigate whether there is significant difference on students’ speaking ability taught without and by using Digital Storytelling of the second-grade students at MAN 1 Pekanbaru. In this quasi-experimental research, the researcher applied total sampling. This research was held on September-November 2024. The total of population were 53 students. Where the class XI Bahasa 1 as the experimental class consisted of 28 students, and class XI Bahasa 2 as the control class consisted of 25 students. Thus, the total sample were 53 students. To collect the data, the researcher used a speaking test to determine the students’ speaking skill. In analyzing the data, the researcher used Independent Sample T-test formula calculated by using SPSS 23 version. The results of data analysis showed there was a significant different on students’ speaking skill taught without and by using Digital Storytelling, in which Sig (2-tailed) 0.000 had less value than 0.05, then Hₒ is accepted and Hₐ is rejected.